Analisis Pengaruh Tingkat Partisipasi Angkatan Kerja dan Pembentukan Modal Tetap Bruto Terhadap Pertumbuhan Ekonomi di Kota Mataram - Mardiana Nur Ayu Safitri; Hailuddin Hailuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of the Labor Force Participation Rate (LFPR) and Gross Fixed Capital Formation (GFCF) on economic growth in Mataram City during the period 2010–2022. The data used are secondary data obtained from the Central Bureau of Statistics (BPS) and were analyzed using multiple linear regression with the assistance of Eviews 12 software. The results show that partially, LFPR has no significant effect on economic growth, while GFCF has a positive and significant effect. However, simultaneously, both independent variables jointly influence economic growth. These findings indicate that investment growth through GFCF plays a more important role in driving the economic growth of Mataram City compared to labor force participation. Therefore, the local government should strengthen investment policies and productive sector development to achieve sustainable economic growth.